TRACKING THE SPIRIT OF ISLAMIC ANTI-NEOIMPERIALISM IN THE THOUGHTS OF AYATOLLAH ALI KHAMENEI - Dina Yulianti (Sadra International Institute, 2023)
In the 20th century, colonized nations achieved their independence. Nevertheless, the struggle against colonization continues as imperialistic forces have transformed into neoimperialistic powers, maintaining control over economic, political, and cultural aspects. Consequently, the struggles of Third World countries have evolved from physical resistance against colonization to the pursuit of establishing an independent, just governance system that upholds the rights of marginalized populations. This article explores the concept of ‘neoimperialism’ and how the Qur’an views resistance against this neoimperialism, particularly through an examination of the thoughts of the eminent Iranian scholar, Ayatollah Ali Khamenei. One of the key points in Ayatollah Khamenei's thinking is that neoimperialistic powers exploit native elite groups in their quest for dominance and employ neoimperialistic jargon such as modernity, progress, human rights, and democracy. Islam does not inherently oppose these concepts but rather opposes their misuse for the benefit of neoimperialism.